Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Metode Flipped Classroom terhadap Keterampilan Berpikir Kritis - Fitriya Diyan Sari; Lambang Subagiyo; Muliati Syam (Jurnal Penelitian Pendidikan IPA, 2023)
The poor condition of the ability to think critically in students is a concern of the education system for the success of twenty-first-century learning. The combination of the model with the right method during the learning practice is certainly needed in training the ability to think critically. Therefore, to find out the increase in the ability to think critically of students at MAN 1 Samarinda, research was carried out by applying guided inquiry combined with a flipped classroom. The research design is a pretest-posttest match control group research design, because it is a quasi-experimental research type. The research sample consisted of the class receiving treatment and the class not receiving treatment which was determined through sampling using the purposive sampling technique. Measuring students' critical considerations through giving tests in the form of essay questions related to momentum and impulse material. The Mann-Whitney test explained that the class that received treatment experienced a significant increase in the ability to think critically after the guided inquiry learning model was applied combined with the flipped classroom method